Alcohol Consumption is Associated with Poor Health in HIV Clinic Patient Population: A Behavioral Surveillance Study - Shacham, Enbal (2011)
Previous research reports that populations with HIV consume higher rates of alcohol than general population. This cross-sectional study (n = 391) was conducted to measure alcohol consumption, factors associated with consumption, and the relationship between alcohol and HIV viral loads among individuals receiving HIV care. Increased alcohol consumption was associated with being male, lower education attainment, and lacking a current HAART prescription. Additionally, among those currently on HAART, unsuppressed viremia was associated with higher levels of alcohol consumption. These findings suggest that there may be a relatively low level of alcohol consumption that is detrimental to virologic suppression among populations with HIV.